Cultural Studies and Everyday Life: A Balinese Case - Hobart, Mark (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This article aims to bring the intellectual rigour of Cultural Studies to Balinese ideas about culture which confuse culture with ideology. Cultural Studies is not the study of culture, but its critique which deconstructs culture as misrepresenting actuality as an Imaginary convenient to regimes of power. The New Order articulated ‘ kebudayaan ’ to create a submissive populace happy to embrace global tourism. Culture is no longer how how people do things but marketable commodities posturing as ‘ancient tradition’. Bali as paradise is a cliché. The island now fulfils Madame Suharto’s dream of Disneyland. The capitalist fantasy of endless cost-free growth bears no resemblance to the sophisticated Balinese cosmology of Kali-Yuga, which ends in cataclysmic dissolution; or to popular ideas of the world as ceaseless transforming. Although kebudayaan dismisses ordinary people as stupid masses, they often escape the ideological straitjacket of kebudayaan by just getting on with culture as everyday life.